(untitled) (INNOVATIVE ECONOMY, 2026)
Vons I.V. MODERNIZATION OF INVESTMENT MANAGEMENT MECHANISMS OF ORGANIZATIONS WITHIN THE SYSTEM OF ENSURING SUSTAINABLE DEVELOPMENT UNDER CONTEMPORARY TRANSFORMATIONS Purpose. The aim of the article is to substantiate the directions for modernizing the mechanisms of investment activity management of organizations within the system of sustainable development, taking into account the impact of contemporary transformational processes and challenges. Methodology of research. The theoretical and methodological basis of the study includes the provisions of neoclassical investment theory, strategic management theory, institutional economics, and financial management. At the same time, under modern conditions, these approaches require supplementation by the concept of sustainable development, which implies an orientation of investments not only toward the maximization of financial results but also toward achieving long-term social and environmental effects. The methodological framework of the study of investment activity management in the context of sustainable development is also formed by the following scientific approaches: the systems approach, which makes it possible to consider investment management mechanisms as an interconnected set of instruments, procedures, and actors within a unified sustainable development system; the institutional approach, which emphasizes the role of formal and informal institutions, the regulatory environment, and organizational rules in shaping investment behaviour; the strategic approach, which provides for the alignment of investment decisions with the long-term development goals of organizations and the goals of sustainable development; the process approach, within which investment activity management is viewed as a sequence of stages, from identifying investment needs to evaluating outcomes and adjusting managerial decisions; the risk-oriented approach, which ensures consideration of uncertainty as well as investment, financial, institutional, and security risks in making and implementing investment decisions under conditions of contemporary transformations. The integrated application of these approaches made it possible to form a holistic vision of the mechanisms of investment activity management of organizations and to substantiate directions for their modernization within the system of sustainable development. Findings. From the perspective of the goal-oriented approach, the expediency of considering the modernization of investment activity management mechanisms of organizations as a purposeful, multi-level managerial process aimed at achieving the strategic goals of sustainable development is substantiated. It is established that these goals are formed at the intersection of economic, social, and environmental priorities and should be integrated into the system of strategic and investment management of organizations. It is proven that aligning investment decisions with sustainable development goals contributes to increasing the efficiency of investment resource utilization, reducing managerial risks, and strengthening the long-term resilience of organizational development under conditions of contemporary transformations. It is argued that the application of the goal-oriented approach creates methodological prerequisites for the transition from fragmented investment activity management to a systemic, adaptive, and results-oriented model, which involves the integration of institutional, organizational, information-analytical, and value-based components of management. This, in turn, allows investment activity to be considered not only as a tool for achieving financial outcomes but also as an important lever for implementing sustainable development strategies of organizations. Originality. The scientific novelty of the research results consists in the following: the scientific and methodological approach to analysing the modernization of investment activity management mechanisms of organizations within the system of sustainable development has been improved by interpreting it as a multi-level managerial process that combines institutional, organizational, information-analytical, and value-based components. Unlike existing approaches, the proposed approach ensures the systemic integration of investment activity into the mechanisms for achieving the strategic goals of sustainable development and allows investment decisions to be considered not in isolation, but in connection with the long-term social and environmental priorities of organizational development. Practical value. The practical significance of the research results lies in the possibility of applying the proposals formulated in the article regarding the modernization of investment activity management mechanisms of organizations within the system of sustainable development in the managerial practice of public sector organizations and the business sector of the economy. The proposed approaches may be used in the development and adjustment of development strategies of various types of organizations, the formation of investment programs and project portfolios, as well as in the process of making managerial decisions on the allocation of investment resources, taking into account economic, social, and environmental priorities. Key words: sustainable development, strategic approach, public sector organizations, business sector, national economy, investment activity management mechanisms of organizations, transformational processes, investment decisions.